Legal Analysis of Compensation in Land Acquisition for Public Use: A Case Study of Priority Tourism Road Development in Golo Mori Village - Feliks Suwandri; Aartje Tehupeiory; Diana R.W. Napitupulu (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
This study examines the legal aspects of compensation in land acquisition for public interest projects, specifically focusing on the road development project in the priority tourism area of Golo Mori Village, Manggarai Barat Regency. The main objectives are to evaluate the implementation of compensation payments in accordance with applicable laws and regulations, and to identify challenges faced during the land acquisition process in practice. The research employs a normative and empirical juridical approach, collecting data through literature review and interviews with relevant stakeholders, including local government officials, affected communities, and project implementers. The findings of this study are significant for policymakers and land acquisition practitioners, as they provide a foundation for recommendations to improve procedures and regulations, making them more transparent, fair, and protective of the rights of affected communities. Additionally, this research contributes academically by enriching the legal studies on agrarian law and land acquisition in Indonesia, especially regarding justice and legal certainty in compensation processes. The results reveal a gap between existing regulations and their application in the field, including unclear criteria for determining compensation amounts and insufficient community involvement in the acquisition process. These issues potentially lead to social conflicts and hinder the progress of desired development projects. Therefore, policy reform and improvements in land acquisition mechanisms that are more participatory and accountable are necessary to ensure the protection of community rights and the smooth implementation of development